Tere Liye’s Reader in Makassar: Community, Class, and the Social Construction of Literary Taste - Muhammad, Harry Isra; Oddang, Faisal; -, Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This article examines how young readers in Makassar construct and perform literary taste through their engagement with Tere Liye’s popular fiction. Employing Bourdieu’s concepts of field, habitus, and capital, and drawing on in-depth interviews, the study traces how taste is formed at the intersection of family background, school environment, peer networks, religious values, and the symbolic power of the marketplace. The findings reveal that, in contrast to Bourdieu’s classic model, family cultural capital does not neatly determine taste; instead, most participants, regardless of class, encounter fiction through schools and communities rather than at home. Organizational life and reading groups emerge as crucial spaces where social capital is accumulated, boundaries of taste are formed, and readers gain recognition and belonging. The commercial dominance of publishers and bookstores further shapes what is visible and legitimate, while the motivational and Islamic themes in Tere Liye’s work respond to both neoliberal aspirations and religious ideals. The study highlights the importance of recognizing the agency of readers, the plural sources of legitimacy, and the uneven structures that frame literary taste in contemporary Indonesia, especially Makassar.